Revenue and Expenditure Base of Municipalities at Gandaki Province - Sharma, Devilal; Vyas, Surendra Kumar (Journal of Political Science, 2023)
The funding scheme from federal and provincial government had a positive impact on equity through the formula funding scheme. However, property taxes; house and land tax; house and land rent tax; business tax; rental or lease tax; parking fees; herbs, scraps, wildlife tax and service charges are the main sources of income of municipalities. An efficient revenue base allows local governments to provide reasonably efficient services to their people. By considering this issue, the study served primarily as a quantitative study. Using a descriptive and causal comparative study design, expert opinions on key indicators of income and expenditure, and their relative importance for assessing the financial health of the municipal unit and collect opinions on actions that should be taken to improve through Key Informant Interviews (KII) checklists. The main informants were municipal executive-level officials or elected authorities. A checklist was prepared for KII instruction by considering existing literature and consulting the experts of the related field. Out of the 85 municipalities, 27 municipalities were selected as sampling units. The sample represents approximately 32% of the population. The secondary data required for the study was collected from the Annual Reports and Audit Reports of sample municipalities of the office of the auditor general. Federal and state grants play an important role in supporting local government spending. Overall, local governments have found themselves gradually strengthening their income and expenditure bases to improve their financial viability, putting them on the path to financially sustainable development.